Double-signal molecularly imprinted electrochemical sensor based on Cu / Fe-MOF and AuNPs and preparation method thereof

By introducing Cu/Fe-MOF and AuNPs into electrochemical sensors, combining molecularly imprinted polymers and dual-signal detection systems, the problems of insufficient stability and limited sensitivity in the prior art are solved, and high sensitivity and specific detection are achieved, which is suitable for the detection of aminourea and quantitative analysis of other trace substances.

CN119619251AActive Publication Date: 2025-03-14SHAANXI UNIV OF SCI & TECH
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411780771.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-05
Publication Date
2025-03-14
Estimated Expiration
2044-12-05

AI Technical Summary

Technical Problem

The prior art has problems of insufficient stability and limited sensitivity when detecting aminourea (SEM), which is difficult to meet the needs of high precision and low cost.

Method used

A dual-signal molecular imprinting electrochemical sensor based on Cu/Fe-MOF and AuNPs was used to prepare modified electrodes by hydrothermal method and electrodeposition method, combining molecular imprinting polymer (MIP) and dual-signal detection system to improve the active site and electrochemical performance of the electrode.

Benefits of technology

High sensitivity and specific detection are achieved, with a linear range of 0.005 - 100 nM and a detection limit as low as 0.0039 nM, which significantly improves the stability and accuracy of the detection while reducing costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119619251A_ABST
    Figure CN119619251A_ABST
Patent Text Reader

Abstract

The invention provides a dual-signal molecularly imprinted electrochemical sensor based on Cu / Fe-MOF (Metal Organic Framework) and AuNPs (AuNPs) and a preparation method of the dual-signal molecularly imprinted electrochemical sensor. Carbon cloth is used as a substrate, Cu / Fe-MOF grows in situ, an AuNPs modified electrode is electrically deposited, and a double-signal system is constructed; and preparing the molecularly imprinted polymer film layer by using semicarbazide as a template through electro-polymerization. According to the sensor, high-sensitivity detection of semicarbazide is achieved through double-signal change, the linear range is 0.005-100 nM, and the detection limit is 0.0039 nM. According to the invention, a large specific surface area material and a molecular imprinting technology are combined, so that the detection sensitivity and specificity are improved; the dual-signal mode enhances the detection stability and accuracy; the preparation method is simple, low in cost, suitable for quantitative analysis of trace substances and wide in application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of electrochemical sensors, and in particular to a dual-signal molecular imprinting electrochemical sensor based on Cu / Fe-MOF and AuNPs and a preparation method thereof. Background Art

[0002] As an antimicrobial drug widely used in animal husbandry and aquaculture, NFZ plays an important role in preventing and treating various animal diseases. However, semicarbazide (SEM) produced by the metabolism of NFZ in animals can stably bind to proteins to form potential carcinogenic and teratogenic food-derived residues, posing a threat to human health. Given that SEM is relatively stable after remaining in animals, compared to NFZ itself, the use and distribution of NFZ is usually monitored indirectly by detecting the content of SEM to ensure the safety of animal food.

[0003] At present, traditional methods for analyzing SEM include ultra-high performance liquid chromatography-tandem mass spectrometry, fluorescence, surface-enhanced Raman scattering, etc. Although these methods have certain analytical effects under specific conditions, they are often limited by high operating costs or insufficient sensitivity, and are greatly restricted in practical applications. In contrast, electrochemical methods have become a more promising analytical method due to their advantages such as high precision, high sensitivity, simple operation and low cost. In particular, voltammetry, as an electrochemical and electroanalytical technique based on measuring the relationship between current and applied potential, can efficiently analyze trace substances, has a wide linear range of analytical concentrations, short analysis time, and selectivity for a variety of solvents and electrolytes, and can simultaneously determine multiple analytes without prior separation. Among them, differential pulse voltammetry (DPV) has become one of the most widely used voltammetry methods due to its high efficiency, sensitivity, stability and accuracy in the detection of low-concentration analytes.

[0004] In the field of electrochemical sensors, molecular imprinting layers can provide higher selectivity, which has been reflected in the document with application number "202210043233.4", which introduces a molecular imprinting electrochemical sensor based on a CoMOF-IL sensitive membrane modified electrode and its preparation method and detection method. However, this method still has some problems, such as the insufficient stability of single-signal electrochemical sensors. In order to overcome this defect, a dual-signal mode was introduced, which can reduce the interference of external factors such as environment and temperature by generating electrochemical signals from two different sources, thereby improving the stability and accuracy of detection.

[0005] Although the molecular imprinting layer can improve the selectivity, the molecular imprinting polymer (MIP) layer modified on the electrode surface often hinders electron transfer, resulting in a decrease in sensor sensitivity. Therefore, it is necessary to introduce materials with large specific surface area and excellent charge transfer performance on the electrode surface to increase the active sites on the electrode surface and reduce the electrode charge transfer resistance, thereby improving the detection sensitivity. When Cu / Fe-MOF is used as an electrode material, it can provide abundant coordination sites, providing possibilities for electrode functionalization and electrochemical reactions. In addition, gold nanoparticles (AuNPs) not only have good biocompatibility, but also have good stability and reliable electrocatalytic performance, which can provide an effective electron transfer interface for the electrode, further improving the performance of the sensor.

[0006] In summary, although the existing technology can realize SEM detection to a certain extent, there are still problems such as insufficient stability and limited sensitivity. Therefore, the development of a new type of electrochemical sensor, combining molecular imprinting technology, efficient charge transfer materials and dual signal readout mode, is of great significance for improving the stability, sensitivity and accuracy of detection, and is also an urgent need for current technological development. Summary of the invention

[0007] The present invention provides a dual-signal molecular imprinting electrochemical sensor based on Cu / Fe-MOF and AuNPs and a preparation method thereof, which solves the problems of poor specificity and high cost in the prior art.

[0008] To achieve the purpose of the present invention, the technical solution provided by the present invention is: A method for preparing a dual-signal molecular imprinting electrochemical sensor based on Cu / Fe-MOF and AuNPs, characterized in that it comprises the following steps: Step 1: Prepare modified electrodes: prepare AuNPs and Cu / Fe-MOF modified carbon cloth electrodes AuNPs / Cu / Fe-MOF / CC by hydrothermal method and electrodeposition method; Step 2: Prepare molecular imprinting polymer: add functional monomer and template molecule semicarbazide, use AuNPs / Cu / Fe-MOF / CC as working electrode, and use cyclic voltammetry to electropolymerize MIP: polymerize in PBS solution containing SEM and monomer. After the polymerization is completed, immerse the working electrode in eluent to remove the template; Step 3. The prepared molecular imprinting sensor is used to re-identify targets of different concentrations. The test method is electrochemical method. The CV test potential range is -0.2–0.6 V and -0.2–0.85 V, the DPV test range is -0.2-0.85 V, the EIS test frequency is 0.1 Hz-100 KHz, and the amplitude is 5 mV.

[0009] In the step 1, 1.0-1.5 g of Cu(NO3)·3H2O and 0.05-0.30 g of FeCI3·6H2O are dissolved in 22.5 ml of ultrapure water and stirred until fully dissolved; the aromatic acid is dissolved in 7.5 ml of ethanol and 7.5 ml of DMF and fully dissolved by ultrasonic treatment for 1 hour; then the two solutions are mixed, a water-soluble polymer is added for surface shaping, ultrasonic treatment is continued for 1 hour, a piece of carbon cloth is added, placed in a reactor, and reacted at 100° C. for 6-18 hours; after the reaction is completed, the carbon cloth is taken out, washed alternately with ethanol and ultrapure water, and dried in an oven at 40° C. for 12 hours; and Cu / Fe-MOF / CC is prepared.

[0010] The aromatic acid is one or more of benzoic acid, phthalic acid, trimellitic acid and terephthalic acid.

[0011] In the step 1, 5-20 ml of HAuCI4 solution is used as the electrolyte, Cu / Fe-MOF / CC is used as the working electrode, a platinum sheet is used as the counter electrode, a saturated calomel electrode is used as the reference electrode, the potential is set to -0.2-0.3 V, the electrodeposition is performed for 200-900 s, the electrode surface is rinsed with ethanol and ultrapure water, and the electrode is placed in a 40° C. oven for 12 hours for standby use; and an AuNPs / Cu / Fe-MOF / CC electrode is prepared.

[0012] The specific steps of step 2 are: in a three-electrode system, using cyclic voltammetry to electropolymerize MIP; in a PBS solution containing SEM and monomers, setting the voltage range between 0-1.2V, the rate is 20-200mV / s, and the number of polymerization cycles is 10-30 cycles; immersing the working electrode in a weakly acidic washing solution to elute the template.

[0013] The specific steps of step three are to conduct electrochemical tests in a three-electrode system, using AuNPs / Cu / Fe-MOF / CC as the working electrode, and the test items include CV, DPV and EIS tests; the CV test potential range is -0.2-0.6V and -0.2-0.85V, the DPV test range is -0.2-0.85V, the EIS test frequency is 0.1Hz-100KHz, and the amplitude is 5mV; the tested electrolytes all contain 5mM [Fe(CN)6] 3- / 4- and 0.1 M potassium chloride probe solution.

[0014] The dual-signal molecular imprinting electrochemical sensor based on Cu / Fe-MOF and AuNPs was prepared according to the preparation method described above.

[0015] Compared with the prior art, the advantages of the present invention are: 1. Highly sensitive and specific detection: The present invention introduces electrode modification materials with large specific surface area and excellent charge transfer performance, increases the active sites on the electrode surface, thereby reducing the electrode charge transfer resistance and improving the detection sensitivity. Specifically, the present invention forms a dual-signal detection system by modifying the electrode, and combines the high selectivity of molecular imprinting polymer (MIP) to successfully prepare a highly sensitive electrochemical sensor, which is particularly suitable for the detection of semicarbazide (SEM). Under optimal conditions, the linear range of the sensor reaches 0.005 - 100 nM, and the detection limit is as low as 0.0039 nM, showing extremely high detection sensitivity and specificity.

[0016] 2. Construction of dual-signal detection system: Using carbon cloth as the substrate electrode, in-situ growth of copper-iron-based metal organic framework (Cu / Fe-MOF), induction electrolyte [Fe(CN)6] 3- / 4- A peak current was generated at a specific potential of 0.67 V. At the same time, the in-situ reduction of gold nanoparticles (AuNPs) on the electrode further increased the electrochemical area of ​​the electrode, reduced the charge transfer resistance, and enhanced the current signal at a potential of 0.18 V, thereby constructing a dual-signal detection system and improving the reliability and accuracy of the detection.

[0017] 3. Innovation in material synthesis and electrode modification: The modified electrode was prepared by hydrothermal method and electrodeposition method, which ensured the uniform coverage and tight combination of Cu / Fe-MOF and AuNPs on the surface of carbon cloth. This method is not only simple to operate, but also low-cost and easy to mass produce.

[0018] 4. Application of molecular imprinting polymer: Using SEM as a template molecule, the MIP film layer is prepared by electropolymerization on the modified electrode. The MIP film layer can specifically recognize SEM molecules, resulting in a decrease in the peak intensity of the double signal after adsorption of SEM and an increase in the peak intensity after elution of SEM, thus achieving specific detection of SEM.

[0019] 5. Significant improvement in electrochemical performance: The significant improvement in electrochemical performance of the modified electrode was verified by testing methods such as electrochemical impedance spectroscopy (EIS), cyclic voltammetry (CV) and differential pulse voltammetry (DPV). In particular, the introduction of AuNPs significantly reduced the charge transfer resistance of the electrode, enhanced the current signal, and improved the response speed and sensitivity of the sensor.

[0020] 6. Broad application prospects: The electrochemical sensor prepared by the present invention is not only suitable for the detection of semicarbazide, but can also be extended to the quantitative analysis of other trace substances. Due to its advantages of high sensitivity, specificity and low cost, it has broad application prospects in the fields of environmental monitoring, food safety, drug analysis, etc.

[0021] In summary, the advantages of the present invention are mainly reflected in high sensitivity and specificity detection, construction of dual signal detection system, innovation of material synthesis and electrode modification, application of molecular imprinting polymer, significant improvement of electrochemical performance and broad application prospects, etc. These advantages together constitute the core competitiveness of the present invention and provide new ideas and methods for the development of electrochemical sensors. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 A and B in the figure are SEM images of Cu / Fe-MOF / CC and AuNPs / Cu / Fe-MOF / CC, respectively.

[0023] Figure 2 The middle ones are the XRD test results of CC, Cu / Fe-MOF / CC and AuNPs / Cu / Fe-MOF / CC.

[0024] Figure 3 This is the XPS graph of AuNPs / Cu / Fe-MOF / CC.

[0025] Figure 4 EIS tests of CC, Cu / Fe-MOF / CC and AuNPs / Cu / Fe-MOF / CC.

[0026] Figure 5 CV tests and linear equations of CC, Cu / Fe-MOF / CC and AuNPs / Cu / Fe-MOF / CC at different scan rates.

[0027] Figure 6 The stability of AuNPs / Cu / Fe-MOF / CC was tested electrochemically.

[0028] Figure 7 It is the EIS test during the working process of MIP / AuNPs / Cu / Fe-MOF / CC.

[0029] Figure 8 It is the DPV test during the working process of MIP / AuNPs / Cu / Fe-MOF / CC.

[0030] Fig. 9 It is the DPV test and detection linear range of the sensor to detect different concentrations of semicarbazide. DETAILED DESCRIPTION

[0031] The method of the present invention is described below by specific examples and drawings, but the present invention is not limited thereto. The experimental methods described in the following examples are conventional methods unless otherwise specified, and the reagents and materials are commercially available unless otherwise specified.

[0032] Example 1 A method for preparing a dual-signal molecular imprinting electrochemical sensor based on Cu / Fe-MOF and AuNPs comprises the following steps: Step 1: Preparation of modified electrode: Hydrophilic treatment of carbon cloth: 1×2 cm CC was soaked in a mixed solution of 10% nitric acid and sulfuric acid (v / v=3 / 1). After 3 days, it was washed alternately with water and ethanol and set aside.

[0033] Preparation of Cu / Fe-MOF / CC: Dissolve 1.033g of Cu(NO3)·3H2O and 0.25g of FeCI3·6H2O in 22.5ml of ultrapure water and stir until fully dissolved. Dissolve 0.1g of benzenetricarboxylic acid in 7.5ml of ethanol and 7.5ml of DMF and sonicate for 1h to fully dissolve. Then mix the two solutions, add 1ml (1g / L) of the polymer compound PEI for surface shaping and continue sonicating for 1h, add a piece of carbon cloth, place it in a reactor, and react at 100℃ for 12h. After the reaction is completed, take out the carbon cloth, wash it alternately with ethanol and ultrapure water, and dry it in a 40℃ oven for 12h.

[0034] Preparation of AuNPs / Cu / Fe-MOF / CC: Use 10 ml HAuCI4 (10 mM) solution as electrolyte, Cu / Fe-MOF / CC as working electrode, platinum sheet as counter electrode, saturated calomel electrode as reference electrode, set the potential to 0.15 V, electrodeposit for 600 s, rinse the electrode surface with ethanol and ultrapure water, and place in a 40 °C oven for 12 h for later use.

[0035] Step 2: Preparation of molecularly imprinted polymer (MIP) using resorcinol and template molecule semicarbazide (SEM): MIP was electropolymerized using cyclic voltammetry. The voltage was 0–0.8 V and 50 mV / s for 20 cycles in a PBS (0.1 M, pH 6) solution containing SEM (1.5 mM) and phenol monomers. The working electrode was immersed in the elution solution (v / v = 9 / 1) to elute the template.

[0036] Step 3: Use electrochemical method to analyze the performance of molecular imprinting electrochemical sensor: The working process of molecular imprinting electrochemical sensor was characterized by electrochemical method. The CV test potential range was -0.2–0.6V and -0.2–0.85V, the DPV test range was -0.2-0.85V, the EIS test frequency was 0.1Hz-100KHz, and the amplitude was 5mV. The electrolytes tested all contained 5mM [Fe(CN)6] 3- / 4-and 0.1M potassium chloride probe solution. After the template molecules were adsorbed on MIP / AuNPs / Cu / Fe-MOF / CC, the total difference before and after adsorption was tested by DPV to indirectly reflect the concentration of the analyte. In order to test the electrocatalytic activity of different electrodes, 5mM [Fe(CN)6] 3- / 4- and 0.1 M KCl as the electrolyte for EIS tests.

[0037] Comparison Example Preparation of non-imprinted polymer: No template molecule SEM was added to the polymerization solution, and the above experimental steps were repeated. Non-imprinted was used as a control group to reflect the difference between the polymerized monomer and the polymerized molecularly imprinted polymer.

[0038] Example 2 A method for preparing a dual-signal molecular imprinting electrochemical sensor based on Cu / Fe-MOF and AuNPs comprises the following steps: Step 1: Preparation of modified electrode: Hydrophilic treatment of carbon cloth: 1×2 cm CC was soaked in a mixed solution of 10% nitric acid and sulfuric acid (v / v=3 / 1). After 3 days, it was washed alternately with water and ethanol and set aside.

[0039] Preparation of Cu / Fe-MOF / CC: Dissolve 1.0g of Cu(NO3)·3H2O and 0.05g of FeCI3·6H2O in 22.5ml of ultrapure water and stir until fully dissolved. Dissolve 0.1g of benzoic acid in 7.5ml of ethanol and 7.5ml of DMF and sonicate for 1h to fully dissolve. Then mix the two solutions, add 0.5ml of polyvinyl alcohol (1g / L) and continue sonicating for 1h, add a piece of carbon cloth, place it in a reactor, and react at 100℃ for 12h. After the reaction is completed, take out the carbon cloth, wash it alternately with ethanol and ultrapure water, and dry it in a 40℃ oven for 12h.

[0040] Preparation of AuNPs / Cu / Fe-MOF / CC: Use 5 ml HAuCI4 (10 mM) solution as electrolyte, Cu / Fe-MOF / CC as working electrode, platinum sheet as counter electrode, saturated calomel electrode as reference electrode, set the potential to -0.2 V, electrodeposit for 900 s, rinse the electrode surface with ethanol and ultrapure water, and place in a 40 °C oven for 12 h for later use.

[0041] Step 2: Preparation of molecularly imprinted polymer (MIP) using o-phenylenediamine and template molecule semicarbazide (SEM): MIP was electropolymerized using cyclic voltammetry. The voltage was 0–1.0 V and 200 mV / s for 10 cycles in a PBS (0.1 M, pH 6) solution containing SEM (0.5 mM) and monomers. The working electrode was immersed in an elution solution (v / v = 9 / 1) to elute the template.

[0042] Step 3: Use electrochemical method to analyze the performance of molecular imprinting electrochemical sensor: The working process of molecular imprinting electrochemical sensor was characterized by electrochemical method. The CV test potential range was -0.2–0.6V and -0.2–0.85V, the DPV test range was -0.2-0.85V, the EIS test frequency was 0.1Hz-100KHz, and the amplitude was 5mV. The electrolytes tested all contained 5mM [Fe(CN)6] 3- / 4- and 0.1M potassium chloride probe solution. After the template molecules were adsorbed on MIP / AuNPs / Cu / Fe-MOF / CC, the total difference before and after adsorption was tested by DPV to indirectly reflect the concentration of the analyte. In order to test the electrocatalytic activity of different electrodes, 5mM [Fe(CN)6] 3- / 4- and 0.1 M KCl as the electrolyte for EIS tests.

[0043] Example 3 A method for preparing a dual-signal molecular imprinting electrochemical sensor based on Cu / Fe-MOF and AuNPs comprises the following steps: Step 1: Preparation of modified electrode: Hydrophilic treatment of carbon cloth: 1×2 cm CC was soaked in a mixed solution of 10% nitric acid and sulfuric acid (v / v=3 / 1). After 3 days, it was washed alternately with water and ethanol and set aside.

[0044] Preparation of Cu / Fe-MOF / CC: Dissolve 1.5g of Cu(NO3)·3H2O and 0.30g of FeCI3·6H2O in 22.5ml of ultrapure water and stir until fully dissolved. Dissolve 0.1g of benzoic acid in 7.5ml of ethanol and 7.5ml of DMF and sonicate for 1h to fully dissolve. Then mix the two solutions, add 3.0ml of polyvinyl alcohol (1g / L) and continue sonicating for 1h, add a piece of carbon cloth, place it in a reactor, and react at 100℃ for 12h. After the reaction is completed, take out the carbon cloth, wash it alternately with ethanol and ultrapure water, and dry it in a 40℃ oven for 12h.

[0045] Preparation of AuNPs / Cu / Fe-MOF / CC: Use 20 ml HAuCI4 (10 mM) solution as electrolyte, Cu / Fe-MOF / CC as working electrode, platinum sheet as counter electrode, saturated calomel electrode as reference electrode, set the potential to 3.0 V, electrodeposit for 200 s, rinse the electrode surface with ethanol and ultrapure water, and place in a 40 °C oven for 12 h for later use.

[0046] Step 2: Preparation of molecularly imprinted polymer (MIP) using o-phenylenediamine and template molecule semicarbazide (SEM): MIP was electropolymerized using cyclic voltammetry. The voltage was 0–1.2 V and 20 mV / s for 30 cycles in a PBS (0.1 M, pH 6) solution containing SEM (2.5 mM) and monomers. The working electrode was immersed in an elution solution (v / v = 9 / 1) to elute the template.

[0047] Step 3: Use electrochemical method to analyze the performance of molecular imprinting electrochemical sensor: The working process of molecular imprinting electrochemical sensor was characterized by electrochemical method. The CV test potential range was -0.2–0.6V and -0.2–0.85V, the DPV test range was -0.2-0.85V, the EIS test frequency was 0.1Hz-100KHz, and the amplitude was 5mV. The electrolytes tested all contained 5mM [Fe(CN)6] 3- / 4- and 0.1M potassium chloride probe solution. After the template molecules were adsorbed on MIP / AuNPs / Cu / Fe-MOF / CC, the total difference before and after adsorption was tested by DPV to indirectly reflect the concentration of the analyte. In order to test the electrocatalytic activity of different electrodes, 5 mM [Fe(CN)6] 3- / 4- and 0.1 M KCl as the electrolyte for EIS tests.

[0048] Based on the electrochemical sensor prepared in Example 1, its performance was analyzed, and the specific method is as follows.

[0049] The best performance parameters were selected to prepare the sensing platform, and the DPV method was used to measure the [Fe(CN)6] 3- / 4- The performance of the MIP / AuNPs / Cu / Fe-MOF / CC electrochemical sensor was analyzed in the probe solution. As the SEM concentration increased, it continuously occupied the imprinting cavity, hindering the electron transfer on the sensing platform, resulting in a decrease in the first pair of current peaks. At the same time, the active centers provided by the metal in MIP / AuNPs / Cu / Fe-MOF / CC were occupied, resulting in a decrease in the second pair of current peaks. Using ΔI D (ΔI D=ΔI1+ΔI2) reflects the concentration of adsorbed template molecules. The test results of different concentrations were analyzed. The test results showed that the concentration range of MIP / AuNPs / Cu / Fe-MOF / CC adsorption SEM was 5×10 -12 - 1×10 -7 M, the dual signal current response is linearly related to the concentration, and the linear equation is ΔI D = 0.0842 log C + 1.0290 (R 2 =0.9979), the detection limit was 3.9 × 10 -12 M (S / N =3).

[0050] The test performance of the dual-signal molecular imprinting electrochemical sensor based on AuNPs and Cu / Fe-MOF obtained in the embodiment for semicarbazide is as follows: Figure 1 A and B in the figure are SEM images of Cu / Fe-MOF / CC and AuNPs / Cu / Fe-MOF / CC, respectively. SEM was used to analyze the structural composition during the electrode preparation process. The test observed that AuNPs and Cu / Fe-MOF were evenly covered on the surface of the carbon cloth, the specific surface area of ​​the electrode increased, and the modification of the two materials provided more electron transfer channels for the electrode. The carbon cloth formed a dense material layer on the surface by hydrothermal growth of Cu / Fe-MOF / CC and electrodeposition of AuNPs, proving the successful synthesis of the two materials.

[0051] Figure 2 The XRD test results of CC, Cu / Fe-MOF / CC and AuNPs / Cu / Fe-MOF / CC are shown in the figure. It can be seen that the crystal plane information of Cu / Fe-MOF grown by hydrothermal method and Cu-MOF simulation diffraction peaks are similar, which confirms that Cu / Fe-MOF is successfully synthesized on the carbon cloth surface. AuNPs / Cu / Fe-MOF / CC was prepared by electrodeposition, and the test results were consistent with the standard simulation peak information of Au. No other impurity peaks were detected in the test results, which proved that the target material was successfully synthesized on the electrode.

[0052] Figure 3 This is the full XPS spectrum information of AuNPs / Cu / Fe-MOF / CC. The expected elements can be seen, among which the N element comes from PEI in the electrode preparation process and the O element comes from the aromatic acid ligand.

[0053] Figure 4EIS test of CC, Cu / Fe-MOF / CC and AuNPs / Cu / Fe-MOF / CC. EIS test was performed in the probe solution to study the change of charge transfer resistance at the electrode interface during the electrode modification process. The results showed that the charge transfer resistance of the electrode gradually decreased during the gradual modification of the material on the carbon cloth. This is due to the excellent electrocatalytic performance of AuNPs and Cu / Fe-MOF, which catalyzed the reaction of the probe solution at the electrode interface and gradually increased the conductivity of the electrode material.

[0054] Figure 5 The CV test and linear equation of CC, Cu / Fe-MOF / CC and AuNPs / Cu / Fe-MOF / CC at different scan rates. The test results of the three electrodes show that the electrode peak current is linearly related to the square root of the scan rate, indicating that the electrolyte is a diffusion-controlled reaction process on the electrode surface. In the process of modifying the material on the carbon cloth surface, the redox peak current increases at the same rate, indicating that the electrochemical active area continues to increase.

[0055] Figure 6 The stability of AuNPs / Cu / Fe-MOF / CC was electrochemically tested. In order to ensure the stability of the sensor, the sensing material must be able to be repeatedly tested. The test process was to continuously treat it in the eluent for several times, and then perform a DPV test. The test results showed that the prepared AuNPs / Cu / Fe-MOF / CC electrode had strong stability. After 20 consecutive treatments and tests, the electrochemical response produced hardly changed.

[0056] Figure 7 This is the EIS test of MIP / AuNPs / Cu / Fe-MOF / CC during operation. EIS is used to characterize the changes in charge transfer resistance during sensor preparation and operation. The results show that the charge transfer resistance decreases continuously during the preparation of the material. After the molecular imprinting polymer is polymerized, a group fault is generated on the electrode interface. The charge transfer of the electrolyte is hindered during the electrochemical reaction, resulting in an increase in the charge transfer resistance, which decreases after the template molecules are washed off.

[0057] Figure 8 This is a DPV test during the working process of MIP / AuNPs / Cu / Fe-MOF / CC. The test results show that during the modification of the material, the electrode catalytic performance continues to increase and the current response of the probe solution continues to increase. After the modification of Cu / Fe-MOF, a new current response appears, forming a dual-signal electrochemical sensing system. After the molecular imprinting polymer is prepared on the AuNPs / Cu / Fe-MOF / CC electrode, the two current signals decrease at the same time. After the template molecules are removed, the current peaks increase at the same time. The sensor signal readout method is the sum of the difference between the two current signals.

[0058] Fig. 9 The DPV test and linear range of the sensor for detecting different concentrations of semicarbazide. The test results (Fig. 6.B) show that the concentration range of semicarbazide adsorbed by MIP / AuNPs / Cu / Fe-MOF / CC is 5×10 -12 -1×10 -7 M, the dual signal current response is linearly related to the concentration, and the linear equation is ΔI D =0.0842logC+1.0290(R 2 =0.9979), the detection limit is 3.9×10 -12 M.

[0059] Through the detailed results illustrated in the attached figures, it can be intuitively seen that the dual-signal molecular imprinting electrochemical sensor based on Cu / Fe-MOF and AuNPs has achieved successful synthesis of materials, clear structural characteristics and significant improvement of electrochemical performance during the preparation process. The SEM image shows that the modified material evenly covers the surface of the carbon cloth and forms a dense morphology. XRD and XPS analysis verify the successful synthesis of the target material and the presence of the expected elements. The results of EIS, CV and stability tests show that the electrode material has excellent electrocatalytic performance and stability. In the electrochemical behavior test of the working process, the sensor showed obvious changes in dual-signal response and detection capabilities in a wide linear range, which fully demonstrated its advantages in high sensitivity and specific detection. These attached results jointly demonstrate the significant beneficial effects of this patented technical solution in the field of electrochemical sensors.

[0060] The above embodiments are only preferred technical solutions of the present invention and are not to be regarded as limitations of the present invention. The protection scope of the present invention shall be the technical solutions recorded in the claims, including equivalent replacement solutions of the technical features in the technical solutions recorded in the claims, that is, equivalent replacement improvements within this scope are also within the protection scope of the present invention.

Claims

1. A method for preparing a dual-signal molecular imprinting electrochemical sensor based on Cu / Fe-MOF and AuNPs, characterized in that: The following steps are involved: Step 1: Prepare modified electrodes: prepare AuNPs and Cu / Fe-MOF modified carbon cloth electrodes AuNPs / Cu / Fe-MOF / CC by hydrothermal method and electrodeposition method; Step 2: Prepare molecular imprinting polymer: add functional monomer and template molecule semicarbazide, use AuNPs / Cu / Fe-MOF / CC as working electrode, and use cyclic voltammetry to electropolymerize MIP: polymerize in PBS solution containing SEM and monomer. After the polymerization is completed, immerse the working electrode in eluent to remove the template; Step 3. The prepared molecular imprinting sensor is used to re-identify targets of different concentrations. The test method is electrochemical method. The CV test potential range is -0.2–0.6 V and -0.2–0.85 V, the DPV test range is -0.2-0.85 V, the EIS test frequency is 0.1 Hz-100 KHz, and the amplitude is 5 mV.

2. The method for preparing a dual-signal molecular imprinted electrochemical sensor based on Cu / Fe-MOF and AuNPs according to claim 1, characterized in that: In the step 1, 1.0-1.5 g of Cu(NO3)·3H2O and 0.05-0.30 g of FeCI3·6H2O are dissolved in 22.5 ml of ultrapure water and stirred until fully dissolved; the aromatic acid is dissolved in 7.5 ml of ethanol and 7.5 ml of DMF and fully dissolved by ultrasonic treatment for 1 hour; then the two solutions are mixed, a water-soluble polymer is added for surface shaping, ultrasonic treatment is continued for 1 hour, a piece of carbon cloth is added, placed in a reactor, and reacted at 100° C. for 6-18 hours; after the reaction is completed, the carbon cloth is taken out, washed alternately with ethanol and ultrapure water, and dried in an oven at 40° C. for 12 hours; and Cu / Fe-MOF / CC is prepared.

3. The method for preparing a dual-signal molecular imprinted electrochemical sensor based on Cu / Fe-MOF and AuNPs according to claim 2, characterized in that: The aromatic acid is one or more of benzoic acid, phthalic acid, trimellitic acid and terephthalic acid.

4. The method for preparing a dual-signal molecular imprinted electrochemical sensor based on Cu / Fe-MOF and AuNPs according to claim 1, characterized in that: In the step 1, 5-20 ml of HAuCI4 solution is used as the electrolyte, Cu / Fe-MOF / CC is used as the working electrode, a platinum sheet is used as the counter electrode, a saturated calomel electrode is used as the reference electrode, the potential is set to -0.2-0.3 V, the electrodeposition is performed for 200-900 s, the electrode surface is rinsed with ethanol and ultrapure water, and the electrode is placed in a 40° C. oven for 12 hours for standby use; and an AuNPs / Cu / Fe-MOF / CC electrode is prepared.

5. The method for preparing a dual-signal molecular imprinted electrochemical sensor based on Cu / Fe-MOF and AuNPs according to claim 1, characterized in that: The specific steps of step 2 are: in a three-electrode system, using cyclic voltammetry to electropolymerize MIP; in a PBS solution containing SEM and monomers, setting the voltage range between 0-1.2V, the rate is 20-200mV / s, and the number of polymerization cycles is 10-30 cycles; immersing the working electrode in a weakly acidic washing solution to elute the template.

6. The method for preparing a dual-signal molecular imprinted electrochemical sensor based on Cu / Fe-MOF and AuNPs according to claim 1, characterized in that: The specific steps of step three are to conduct electrochemical tests in a three-electrode system, using AuNPs / Cu / Fe-MOF / CC as the working electrode, and the test items include CV, DPV and EIS tests; the CV test potential range is -0.2-0.6V and -0.2-0.85V, the DPV test range is -0.2-0.85V, the EIS test frequency is 0.1Hz-100KHz, and the amplitude is 5mV; the tested electrolytes all contain 5mM [Fe(CN)6] 3- / 4- and 0.1 M potassium chloride probe solution.

7. A dual-signal molecular imprinting electrochemical sensor based on Cu / Fe-MOF and AuNPs prepared according to the preparation method of claim 1.

Citation Information

Patent Citations

  • Molecularly imprinted electrochemical sensor of CoMOF-IL sensitive membrane modified electrode as well as preparation method and detection method of molecularly imprinted electrochemical sensor

    CN116482199A

  • Construction of Fe MOF-CS molecularly imprinted electrochemical sensor and application of Fe MOF-CS molecularly imprinted electrochemical sensor in acrylamide detection

    CN117309959A

  • Molecularly imprinted sensor for detecting trace norfloxacin and preparation and detection method thereof

    CN118330202A

  • Molecular imprinting ratio electrochemical sensor based on F-beta-FeOOH NRs as well as preparation method and detection method of molecular imprinting ratio electrochemical sensor

    CN118501221A